Export Analysis and Forecasting Models - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Galinienė, Birutė; Visokavičienė, Birutė (Ekonomika, 2002)
There is a model for Lithuanian export sector suggested in this research. Based on the presumption that the efficiency of export depends on many micro, meso and macrolevel environmental variables, the aim was to develop a model for Lithuanian export. The model would determine rational variables by undertaking an analysis of the micro, meso and macrolevel environment affecting export and recommend the increase of the export’s competitiveness. The analysis of the export sector in developed countries and Lithuania allows for the identification of the areas where the situation in Lithuania is comparable, partly comparable with or quite different from the level attained by developed countries. The data of this analysis can be used in identifying export development trends in developed countries and further provide recommendations for Lithuania. To demonstrate the application of the research, recommendations for the improvement of the export will be presented in this paper.